2019
DOI: 10.1002/glia.23668
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte involvement in Gulf War Illness

Abstract: Low level sarin nerve gas and other anti‐cholinesterase agents have been implicated in Gulf War illness (GWI), a chronic multi‐symptom disorder characterized by cognitive, pain and fatigue symptoms that continues to afflict roughly 32% of veterans from the 1990–1991 Gulf War. How disrupting cholinergic synaptic transmission could produce chronic illness is unclear, but recent research indicates that acetylcholine also mediates communication between axons and oligodendrocytes. Here we investigated the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Our results show that autoantibodies to neural proteins can be used as biomarkers for diagnosis and prognosis of GWI and may also provide insight into the potential mechanisms of GWI. The only consistent risk factors for GWI are environmental exposures, including the use of pyridostigmine bromide pills and pesticides, which are now known to adversely affect the CNS in significant or combined dosages [ 14 , 15 , 17 , 18 , 19 , 20 , 24 , 25 , 26 , 27 , 28 ]. Although a total of over 50 pesticide products were used during the Gulf War, less than 20 were designated as “pesticides of concern” by the Department of Defense, including the insecticides permethrin and lindane as well as the repellant, DEET ( N , N -diethyl- m -toluamide) and organophosphate insecticides and nerve gases, sarin and cyclosarin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that autoantibodies to neural proteins can be used as biomarkers for diagnosis and prognosis of GWI and may also provide insight into the potential mechanisms of GWI. The only consistent risk factors for GWI are environmental exposures, including the use of pyridostigmine bromide pills and pesticides, which are now known to adversely affect the CNS in significant or combined dosages [ 14 , 15 , 17 , 18 , 19 , 20 , 24 , 25 , 26 , 27 , 28 ]. Although a total of over 50 pesticide products were used during the Gulf War, less than 20 were designated as “pesticides of concern” by the Department of Defense, including the insecticides permethrin and lindane as well as the repellant, DEET ( N , N -diethyl- m -toluamide) and organophosphate insecticides and nerve gases, sarin and cyclosarin [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased autoantibodies of biomarkers NFP, tau, tubulin, and MBP, and neuronal cytoskeletal disruptions, including microtubule instability, axonal degeneration, and altered axonal transport, have been found in many cell and animal studies of toxicant-induced models of GWI [ 27 , 42 , 43 , 44 , 45 , 49 , 52 , 53 , 54 ]. We are only aware of the following prior studies, including our prior pilot study, showing increased autoantibodies in much smaller pilot studies of GW veteran blood samples [ 12 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While no changes have been observed in astrocytes or microglia, the brain’s primary immune cells, in the acute time points following exposure in this model ( O’Callaghan et al, 2015 ), Belgrad et al (2019) found that DFP alone had effects on oligodendrocytes, another glial cell type with immune function ( Peferoen et al, 2014 ). In this study, DFP exposure decreased the number of mature and proliferating oligodendrocytes in the rat cortex and corpus callosum out to 21 days post-exposure while combined CORT and DFP exposure ameliorated these effects.…”
Section: Introductionmentioning
confidence: 53%
“…Deployed soldiers were exposed to significant physiological stressors such as exercise and extreme temperatures ( Young et al, 1992 ; Sapolsky, 1998 ; Sullivan et al, 2003 ) that had the potential to interact with or modulate the responses to chemical exposures. As such, several studies investigating the contribution of nerve agent exposure to GWI have found positive correlations to illness symptomology when sarin surrogates have been combined with a stressor ( O’Callaghan et al, 2015 ; Locker et al, 2017 ; Ashbrook et al, 2018 ; Koo et al, 2018 ; Miller et al, 2018 ; Craddock et al, 2018 ; Michalovicz et al, 2019 ; Belgrad et al, 2019 ). In this GWI rodent model, a single dose of DFP is preceded by a chronic (4–7 day) exposure to exogenous corticosterone (CORT) provided in the drinking water (200 mg/L) to mimic the high physiological stress experienced by soldiers during deployment.…”
Section: Introductionmentioning
confidence: 99%